2014
DOI: 10.4314/gmj.v48i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of glaucoma in the greater Accra Metropolitan Area of Ghana

Abstract: Background: Creatinine (Cr) has been implicated as an independent predictor of hypertension and exercise has been reported as adjunct therapy for hypertension. The purpose of the present study was to investigate the effect of continuous training programme on blood pressure and serum creatinine concentration in black African subjects with hypertension. Methods: Three hundred and fifty seven male patients with mild to moderate (systolic blood pressure [SBP] between 140-180 & diastolic blood pressure [DBP] betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
(17 reference statements)
3
5
0
Order By: Relevance
“…There are mixed reports on the effect of gender on glaucoma prevalence. The present study found no significant difference in glaucoma prevalence between male and females, which was similar to previous studies from Ghana [ 44 , 45 ]. In contrast, studies from Nigeria [ 5 , 40 , 41 ], Ghana [ 46 ] and South Korea [ 44 ] reported a higher prevalence in men than women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There are mixed reports on the effect of gender on glaucoma prevalence. The present study found no significant difference in glaucoma prevalence between male and females, which was similar to previous studies from Ghana [ 44 , 45 ]. In contrast, studies from Nigeria [ 5 , 40 , 41 ], Ghana [ 46 ] and South Korea [ 44 ] reported a higher prevalence in men than women.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found no significant difference in glaucoma prevalence between male and females, which was similar to previous studies from Ghana [ 44 , 45 ]. In contrast, studies from Nigeria [ 5 , 40 , 41 ], Ghana [ 46 ] and South Korea [ 44 ] reported a higher prevalence in men than women. Moreover, gender predilection of glaucoma has not been established suggesting the need for more studies to determine the association of glaucoma with gender.…”
Section: Discussionsupporting
confidence: 93%
“…Glaucoma is asymptomatic until the relatively late stages of disease. This often leads to delayed presentation in Africa where understanding of the disease and access to health care may be limited, often too late to offer sight-saving therapy in 1 or both eyes 10–12. Treatment of glaucoma depends on the stage of disease at presentation, local availability of different interventions, and their relative acceptability to patients.…”
mentioning
confidence: 99%
“…To design a practical tailored strategy for glaucoma management in SSA, it is important to have an in-depth understanding of local differences in presentation across the region. Existing studies have reported the severity of glaucoma at presentation in various African countries, in some reports with 21%–56% blind (<6/60) in the better-seeing eye 10–15. These have mostly been conducted in single clinics using different grading systems,13–16 making it difficult to compare the stage at presentation across different settings or to acquire a comprehensive picture across SSA.…”
mentioning
confidence: 99%
See 1 more Smart Citation